Isotope constraints on nitrogen dynamics in the upper water column of the South China Sea - Yan, Xiuli; Yang, Jin-Yu Terence; Xu, Min Nina; Tan, Ehui; Zheng, Zhenzhen; Zou, Wenbin; Dai, Minhan; Kao, Shuh-Ji (Frontiers in Marine Science, 2022)
The supply of nitrogen (N) from various external and internal sources into the euphotic zone, e.g., atmospheric N deposition (AND), upwelling, lateral intrusion, and remineralization, modulates the biogeochemical and climatic roles of oligotrophic oceans and complicates N dynamics in the upper water column (≤200 m). However, our ability to resolve the mechanisms controlling upper-ocean N cycling is limited by the lack of high-resolution vertical observations. Here, we analyzed concentrations and dual isotopes of nitrate (NO3–) in the upper 200 m of the oligotrophic South China Sea. By examining dual isotopic signatures of NO3– (δ15NNO3 and δ18ONO3) and multiple associated parameters vertically throughout the upper water column, we resolved the dominant N sources and processes, including AND/N2-fixation, assimilative fractionation, and nitrification, and quantitatively evaluated their contributions in the vertical distribution of NO3–, which can be separated into the Δδ18ONO3-positive (δ18ONO3−obs−δ18ONO3−200m>0) and Δδ18ONO3-negative layers (δ18ONO3−obs−δ18ONO3−200m<0) according to the deviation in δ18ONO3 at a given depth (δ18ONO3-obs) from that at 200 m (δ18ONO3-200m). In the Δδ18ONO3-positive layer, the NO3– assimilated by phytoplankton was largely sourced from nitrification (39 ± 11%) and AND/N2 fixation (17-28%), whereas these two processes accounted for 17 ± 10% and 7 ± 6% of the total NO3– pool in the Δδ18ONO3-negative layer. Considering a substantial contribution of the regenerated (nitrification-sourced) NO3– to the total NO3– pool especially in the Δδ18ONO3-positive layer, caution should be taken that the new production assessed by the rates of NO3– uptake may be significantly overestimated in the SCS. These findings not only highlight the importance of these biogeochemical processes to NO3– dynamics in the upper water column of marginal seas, but also with important implications for the estimation of biological carbon pump and/or the f-ratio.